Energy security through transboundary cooperation: Case studies of the Southern African power pool (SAPP) and the West African pool (WAPP) - Eyita, Ekeminiabasi Kingsley (My University, 2014)
The failures of regional cooperation in Africa have been attributed to a number of factors ranging from the lack of political will and commitment by African governments to the role of weak institutions and enforcement mechanisms. These approaches to assessing cooperation focus on the internal versus external nexus of African politics. Regional joint-venture initiatives have the potential to resolve most of the pressing issues facing the continent such as energy security. Part of the energy security issue in Africa is the inadequate supply of and lack of access to electricity within sub-Saharan Africa. Therefore engaging the different sub-regional initiatives towards electricity security, this research employs the Stag Hunt Game theory to analyse regional cooperation emerges to mitigating the electricity access problem in the continent. This research report finds that the problem of cooperation does not simply lie in the lack of political will and commitment on the part of governments in Africa; there are other strategic issues concerned. Thus, an examination of two prominent power pools initiative namely the Southern African Power Pool (SAPP) and the West African Power Pool (WAPP) helps to bring to the fore underlying issues that impact negatively on the success of cooperation. As a result, this research argues that regional ‘public good’ should not undermine national self-sufficiency rather; both initiatives should complement each other.